Impact of Particle Size Distribution in the Preform on Thermal Conductivity, Vickers Hardness and Tensile Strength of Copper-Infiltrated AISI H11 Tool Steel - Vetter, Johannes; Beneder, Samuel; Kandler, Moritz; Feyer, Felix; Körner, Carolin; Schmidt, Michael (Materials, 2023)
Spontaneous infiltration of a porous preform by a metallic melt provides the potential of generating metal matrix composites (MMCs) with tailored combinations of material properties at low cost. The bulk of tool inserts for injection molding must sustain high mechanical and thermal loads and simultaneously exhibit high thermal conductivity for efficient temperature control of the mold insert. To fulfill these contradictory requirements, AISI H11 tool steel preforms were infiltrated by liquid copper. The impact of the fine powder fraction (0 wt.% to 15 wt.%) blended to a coarse H11 powder in the preform on thermal conductivity, Vickers hardness and tensile strength was elucidated. The thermal conductivity of the composites could be enhanced by a factor of 1.84 (15 wt.% fine powder) and 2.67 (0 wt.% fine powder) with respect to the sintered H11 tool steel. By adding 15 wt.% fine powder to the coarse host powder, the tensile strength and Vickers hardness of the copper-infiltrated steel were 1066.3 ±108.7 MPa and 366 ± 24 HV1, respectively, whereas the H11 tool steel yielded 1368.5 ± 89.3 MPa and 403 ± 17 HV1, respectively. Based on the results obtained, an appropriate particle size distribution (PSD) may be selected for preform preparation according with the requirements of a future mold inser